Internal fit and marginal adaptation of all-ceramic implant-supported hybrid abutment crowns with custom-milled screw-channels on Titanium-base: in-vitro study - Marwa Wagih Zaky Fouad Fakhr; Hesham Alansary; Eman Ezzat Youssef Hassanien (BMC, 2024)
Abstract Background Advancements in digital dentistry helped in custom-milling screw-channels in implant-supported restorations; however, the fit of these restorations is still unclear especially for contemporary computer aided designing/computer aided manufacturing (CAD/CAM) materials. This study aimed to compare the internal and marginal fit of Ultra translucent multilayered zirconia versus lithium disilicate implant-supported hybrid abutment crowns (HACs) constructed with custom-milled screw-channels on Titanium-base. Materials and methods A total of 24 HACs with custom-milled screw-channels were constructed from lithium disilicate (Group LDS) and Ultra translucent multilayered zirconia (Group UT) using digital workflow (n = 12). The internal and marginal gaps of HACs on their corresponding Titanium-bases were assessed using replica technique and stereomicroscope, respectively. After testing for normality, quantitative data were expressed as mean and standard deviation and compared using independent t-test at a level of significance (P ≤ 0.05). Results There was no statistically significant difference between Group LDS and Group UT in terms of marginal and internal fit. The internal and marginal gaps in both groups were within the accepted values reported in literature. Conclusions UT and LDS HACs with custom-milled screw-channels demonstrated comparable and acceptable internal fit and marginal adaptations to Ti-base, which lied within the range reported in literature.